Peningkatan Hasil Belajar Siswa dalam Pembelajaran Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Think Pair Share (TPS) di Sekolah Dasar - Anggraini, Silvia; Amerta, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
Research on integrated thematic learning in class IV is motivated by the still low student learning outcomes in integrated thematic learning. The purpose of this study is to describe the planning, implementation, and integrated thematic learning outcomes using Cooperative Learning models of Think Pair Share (TPS) type in grade IV SD. This type of research is a classroom action research (CAR) that uses qualitative and quantitative approaches. The subjects of this study were teachers and fourth grade elementary school students with a total of 32 people. The study was conducted in two cycles. The results showed an increase in: a) The average RPP of the first cycle was 80.55% (good) and the second cycle was 94.44% (very good) b) The average implementation of the aspects of the first cycle was 77.27% (good) and second cycle 92.85% (very good), b) The average implementation of the aspects of the first cycle students 74.99% (good), and the second cycle 92.85% (very good), c) Average student learning outcomes cycle I 71.12 and cycle II 82.05. Thus the Cooperative Learning model Think Pair Share (TPS) type can improve learning outcomes Thematic Integrated students of class IV SDN 17 Pakan Kurai BukittinggiKeywords: Think Pair Share (TPS), Learning Outcomes, Integrated Thematic